Access to antiretrovirals: effects of intellectual property protection - Seinfeld, Janice (2009)
Developing countries have been, in most cases, sceptical about the implementation of intellectual property protection (IPP) with the premise that this policy will hurt the coverage of medicines because the price of the drugs will be substantially high. This claim has overlooked the long run effect of IPP and has dismissed the other relevant policies to tackle the low drug coverage in poor countries. In this paper we measure the impact of IPP on Antiretroviral drugs coverage in 59 countries. According to our estimates, an increase in one unit in the IPP, measured by Park-Guinarte index, leads to an increase of 6% in antiretrovirals prices. However, the overall impact of IPP on coverage is positive; in fact, the marginal impact of a unit of increase in IPP on coverage is almost 14%. This is, most likely, due to the proper incentive framework provided by the IPP to create more and better drugs. Our findings also indicate that a key policy to complement the effect of IPP is an adequate level of health expenditure. Our estimates suggest that an increase of 1% in public expenditure on health as percentage of GDP increases by 3% to 4% the level of coverage of antiretrovirals.